Halal food ingredients: sources, classification and nutrition information - Jaswir, Irwandi; Monsur, Hammed Ademola; Octavianti, Fitri; Lestari, Widya (Yamani Angle Sdn Bhd, 2021)
Some food ingredients are accepted almost throughout the world, while some are regionally based. In fact, food researchers and manufacturers are very particular about the type and concentration of specific ingredient to be added in their products and are cognisance of the area that such food products will be supplied. A product might fail to be accepted by the consumer just because the ingredient in it alters the sensory value in such a way that it is not acceptable to the people in that region. In a nutshell, certain ingredients might be admired in a region but experience total rejection in another.